Digital play: The use of creative technologies in the early years - Howell, Jennifer; McDonald, S. (Information Science Reference (IGI Global), 2013)
This chapter showcases a new framework (Technology and Play Framework) for teachers to consider when planning the use of digital technologies in the early years of formal schooling. It also presents the findings from a pilot study conducted with an F-1 (Foundation year and year 1) class in an Australian primary school that demonstrated how this framework could direct the effective use of a specific digital technology in terms of student learning outcomes with particular focus on literacy and numeracy. While play is recognised as an essential component of good practice in early childhood settings, it needs to be reconsidered and aligned to incorporate emerging digital technologies and complementary pedogogical practices in order to support authentic learning.